STUDY OF CRYSTALLIZATION OF MELTED CHARGES BASED ON BASALT - Akhunov Daniyar Bakhtiyarovich (Scientific Impulse, 2023)
This article describes that basalt citadels were taken and examined, and according to the results of an X-ray study, it was established that the main crystalline phase in them consists of anorthite-like solid impurities.